2006
DOI: 10.1002/adsc.200505356
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Free Oxidation of Alcohols at Room Temperature Using Water as Solvent

Abstract: An effective, cheap, environmentally benign and catalyst-free oxidation of alcohols was carried out at room temperature using tetra-n-butylammonium Oxone (TBA-OX) as oxidant with moderate to high selectivity for most of the alcohols using water as the solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Water is considered as a green solvent in chemistry because it is nontoxic, nonflammable, and low-cost. At the same time, some organic reactions can proceed faster and more selectively in water than in traditional organic solvents. Nevertheless, most organic compounds are insoluble in water and are difficult to react, therefore phase-transfer catalysts (PTCs) are required. The PTCs as the soul of the aqueous phase organic reactions burden the important responsibility of transferring the reactant from aqueous or solid phase to the organic phase so that it can encounter the substrate and react …”
Section: Introductionmentioning
confidence: 99%
“…Water is considered as a green solvent in chemistry because it is nontoxic, nonflammable, and low-cost. At the same time, some organic reactions can proceed faster and more selectively in water than in traditional organic solvents. Nevertheless, most organic compounds are insoluble in water and are difficult to react, therefore phase-transfer catalysts (PTCs) are required. The PTCs as the soul of the aqueous phase organic reactions burden the important responsibility of transferring the reactant from aqueous or solid phase to the organic phase so that it can encounter the substrate and react …”
Section: Introductionmentioning
confidence: 99%
“…of IBX is generally used for the oxidation of alcohols) [8]. In a previous report, we described a procedure for the oxidation of alcohols in that we used tetra-n-butyl ammonium Oxone Ò n-Bu 4 NHSO 5 as oxidant [9]. Recently Thottumkara et al demonstrated catalytic use of IBX in the presence of Oxone Ò for the oxidation of primary and secondary alcohols in user-and eco-friendly solvent mixtures [10].…”
mentioning
confidence: 99%
“…In our ongoing research programs, 21,22,[24][25][26][27] we found that in water as medium, palygorskite is active in the oxidation of alcohols in the presence of Oxone ® (2KHSO 5 •KHSO 4 •K 2 SO 4 ). This novel oxidation system could convert a variety of alcohols to the corresponding carbonyl compounds.…”
mentioning
confidence: 99%